KETERAMPILAN BERPIKIR KRITIS SISWA SEKOLAH DASAR PADA MATA PELAJARAN IPS DI KELAS TINGGI - Nofi Anggraeni; Tin Rustini; Yona Wahyuningsih (Universitas Negeri Surabaya, 2022)
Analysis of critical thinking skills of elementary school students in social studies subjects in higher grades. The purpose of this study is to describe students' critical thinking skills in elementary schools, especially grades IV, V, and VI. This research is based on the analysis of research journals in previous years to be the subject of research in this article. Elementary school critical thinking skills which include the use of learning methods used, as well as analyzing the learning process that can be applied related to the development of critical thinking skills or high-level thinking in elementary school students. The discussion in this study discusses the implementation of critical thinking skills in the realm of social science subjects